Pelatihan Pembuatan Tempe Daun Singkong Sebagai Cemilan Bernutrisi Untuk Ibu Hamil Dan Anak-Anak Sebagai Pencegahan Stunting Di Kota Padang Panjang - relin yesika; Yahdian Rasyadi; Amri Bakhtiar; Nanda Rahma Desra; , Antisa Larasari Deflorian; Ardilla Marisya (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
Prevention of stunting in infants and toddlers can be done starting during pregnancy. Nutritional intake in pregnant women can be done by consuming quality food. In an effort to fulfill nutrition for pregnant women and children by consuming nutritious snacks, this service conducted training on making cassava leaf tempeh to the community in the Bukit Surungan village, West Padang Panjang, Padang Panjang City in July 2022. The training activity began with an explanation about the content of cassava leaf tempeh to the trainees and a demonstration of how to make cassava leaves into tempeh with the addition of tempeh yeast. The finished cassava leaf tempeh is fried with tempeh flour and eaten with the trainees. The trainees said that tempeh was delicious and almost the same as tempeh in general. This tempe-making training has been successfully implemented and the community is interested in eating the fried tempeh as a nutritious snackservice activity that has been carried out has achieved its goal of preventing stunting in the city of Padang Panjang.